HIGHER EDUCATION DEVELOPMENT IN CONFLICT CONDITIONS: EVOLUTION FROM KNOWLEDGE SOCIETY TO UNDERSTANDING SOCIETY - Serhii Terepyshchyi; Glib Khomenko ("Scientific Information Agency "Science-technologies-information" LLC, 2020)
Peacebuilding in society is impossible without generating and implementing an effective higher education development strategy. Education representing the ideological and value principles of humanism, democracy, tolerance, dialogue is a powerful tool in the consolidation of a conflict society, its gradual transformation into a society of understanding. In this regard, the role of the teacher in peacebuilding cannot be overestimated. Unfortunately, most politicians prefer to finance short-term projects where certain material benefit can be obtained in a minimum period of time. This is probably one of the major strategic mistakes that can cause extremely negative consequences. In general terms, peace can be compared with a kind of humanitarian deposit that is long-term oriented. Its main dividend is the stable development of a society in which the confidence of individual citizens in each other acts as a metaphorical interest rate. That is, the greater the social trust within society, the greater the likelihood that war will not affect the territorial integrity of a particular state. The level of trust implies the support of state institutions of power from the side of ordinary citizens, as well as interpersonal trust in matters of religion, ethnic and valuebased differences. Universities should increase the level of trust within society, thus advocating as a means of conflict prevention acording to optimistic scenario or social rehabilitation acording to pesimictic scenario. However, public investment in its development should be steadily increased beside grant financial infusions.